Pagetoid reticulosis (epitheliotropic cutaneous T-cell lymphoma) in an adult alpaca (Vicugna pacos). (July 2016) - Hasbach, Andrea E.; Stern, Adam W.
A 9-year-old, intact female alpaca ( Vicugna pacos ) was presented for a second opinion with a 1-year history of nonpruritic, multifocal scaling and crusted cutaneous lesions, mainly involving skin on the face, axillae, and ventral abdomen. Clinical abnormalities were limited to the skin, and the alpaca was otherwise healthy. The initial veterinarian had examined the alpaca, found no evidence of ectoparasites with laboratory testing, and had tried several trial therapies including oral antibiotics, ivermectin, and topical use of betadine solution. At the time of presentation, the lesions had neither improved nor worsened with any attempted therapy, and multiple skin biopsies were collected. Histopathology and immunohistochemical staining findings were consistent with the pagetoid reticulosis type of cutaneous epitheliotropic T-cell lymphoma. Our report describes the clinical, histopathologic, and immunophenotypic features of pagetoid reticulosis epitheliotropic cutaneous T-cell lymphoma in an alpaca.